A calcium channel or angiotensin converting enzyme inhibitor/angiotensin receptor blocker regime to reduced blood pressure variability in acute ischaemic stroke (CAARBS): a feasibility trial - Davison, WJ; Appiah, K; Robinson, TG; McGurgan, IJ; Rothwell, PM; Potter, JF (Elsevier, 2020)
Background: Trials of lowering blood pressure in patients with acute ischaemic stroke not undergoing thrombolysis have not demonstrated improved outcomes with intervention. Rather than absolute levels, it may be that blood pressure variability is important. However, there are no prospective randomised trials investigating the benefit of reducing blood pressure variability in this patient group.